Flute mode instability of rotating plasma - Ilgisonis, V.I.; Lakhin, V.P.; Sorokina, E.A. (Вопросы атомной науки и техники, 2008)
The influence of rotation on flute instability is studied in the frame of one-fluid magnetohydrodynamics. We consider the simplest model of gravitating cylindrical plasma in the straight nonuniform magnetic field to simulate plasma behavior in mirrors. Using linear stability analysis, we derive dispersion equation and integral expression for the increment of instability. In virtue of this expression, it is shown that rotation itself appears to be destabilizing factor due to centrifugal effect; we prove the corresponding theorem in general. Eigenmode structure and the dependence of the threshold on the frequency of rotation are calculated for linear radial profile of the angular velocity. В рамках одножидкостной магнитной гидродинамики исследуется влияние вращения на желобковую неустойчивость. Предполагается простейшая модель цилиндрической гравитирующей плазмы в прямом неоднородном магнитном поле для моделирования поведения плазмы в зеркальных ловушках. С помощью линейного анализа получено дисперсионное уравнение и интегральное выражение для инкремента неустойчивости. Показано, что в данной постановке задачи вращение из-за центробежного эффекта является сугубо дестабилизирующим фактором; в общем случае доказывается соответствующая теорема. Для линейного радиального профиля угловой скорости вращения рассчитана структура собственных мод и зависимость порога неустойивости от частоты вращения. В рамках однорідинної магнітної гідродинаміки досліджується вплив обертання на желобкову нестійкість. Припускається простіша модель циліндричної гравітуючої плазми в прямому неоднорідному магнітному полі для моделювання поведінки плазми в дзеркальних пастках. За допомогою лінійного аналізу отримано дисперсійне рівняння й інтегральний вираз для інкремента нестійкості. Показано, що в такій постановці задачі обертання завдяки центробіжного ефекту є сугубо дестабілізуючим фактором; в загальному випадку доводиться відповідна теорема. Для лінійного радіального профілю кутової швидкості обертання розраховано структуру власних мод та залежність порога нестійкості від частоти обертання.